Relative importance of Farmers’ Characteristics in Predicting their Knowledge about Indigenous Agricultural Practices - Husain, A. Sakeer; Sundaramari, M; Sreekumar, J (Journal of Extension Education, 2017)
This study was conducted to identify the farmers’ characteristics that act as factors in influencing their knowledge on indigenous agricultural practices. The study was conducted in the state of Kerala among 40 farmers each of ten selected horticultural crops. Step wise regression analysis and multiple linear regression analysis were employed to identify the influencing factors. The study revealed that age, farm power status, innovativeness, rational orientation, communication status, and social participation status positively influence knowledge of farmers on indigenous agricultural practices whereas material status, educational status, and family status were the important characteristics of farmers negatively influencing the knowledge of indigenous practices.